ELEMENTARY EDUCATION IN HISPANIC AMERICA DURING THE VICEREGAL CENTURIES - Vega, Maria Luisa (BIBLIOTECA HISPANO-AMERICANA DE DIVULGACION, 1986)
CONTENIDO: V.2 SCHOOLS IN NEW MEXICO, FLORIDA, ARIZONA ANDTEXAS